Conception rate of artificially inseminated Holstein cows affected by cloudy vaginal mucus, under intense heat conditions - Mellado, Miguel; Lara, Laura Maricela; Veliz, Francisco Gerardo; Santiago, Maria Ángeles de; Avendaño-Reyes, Leonel; Meza-Herrera, Cesar; Garcia, José Eduardo (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to obtain prevalence estimates of cloudy vaginal mucus in artificially inseminated Holstein cows raised under intense heat, in order to assess the effect of meteorological conditions on its occurrence during estrus and to determine its effect on conception rate. In a first study, an association was established between the occurrence of cloudy vaginal mucus during estrus and the conception rate of inseminated cows (18,620 services), raised under intense heat (mean annual temperature of 22°C), at highly technified farms, in the arid region of northern Mexico. In a second study, data from these large dairy operations were used to assess the effect of meteorological conditions throughout the year on the occurrence of cloudy vaginal mucus during artificial insemination (76,899 estruses). The overall rate of estruses with cloudy vaginal mucus was 21.4% (16,470/76,899; 95% confidence interval = 21.1–21.7%). The conception rate of cows with clean vaginal mucus was higher than that of cows with abnormal mucus (30.6 vs. 22%). Prevalence of estruses with cloudy vaginal mucus was strongly dependent on high ambient temperature and markedly higher in May and June. Acceptable conception rates in high milk-yielding Holstein cows can only be obtained with cows showing clear and translucid mucus at artificial insemination.